Lactobacillus casei Strain Shirota Alleviates Constipation in Adults by Increasing the Pipecolinic Acid Level in the Gut - Ou, Yangwenshan; Chen, Shanbin; Ren, Fazheng; Zhang, Ming; Ge, Shaoyang; Guo, Huiyuan; Zhang, Hao; Zhao, Liang (Frontiers in Microbiology, 2019)
The benefits of probiotics for constipation are widely accepted, but the mechanisms involving gut metabolites are unclear. In this study, we investigated the effects of Lactobacillus casei strain Shirota (LcS) on constipated patients and revealed that a metabolite mediator is involved in the LcS-induced constipation alleviation. Sixteen constipated patients and 22 non-constipated participants were recruited. The subjects consumed 100 mL of an LcS beverage (108 CFU/mL) per day for 28 days. The faecal non-volatile metabolites were determined by GC/MS, and the targeted metabolites were further verified in a constipated mouse model. In constipated patients, LcS intervention significantly improved defecation frequency (from 4.81 to 7.81 times per week, p < 0.05), stool consistency (from 2.52 to 3.68, p < 0.05) and constipation-related symptoms. A total of 14 non-volatile faecal metabolites were obtained as potential constipation-related metabolites that were regulated by LcS. Among these metabolites, pipecolinic acid (PIPA) had a significant positive correlation with defecation frequency in constipated patients. PIPA significantly promoted the small intestinal propulsive rate (from 25.45% to 39.68%) and increased the number of faecal pellets (from 30.38 to 57.38 pellets) in constipated mice (p < 0.05). The 5-Hydroxytryptamine (5-HT) and acetylcholine (ACh) in colonic tissue may be partly involved in PIPA-mediated constipation alleviation. In conclusion, PIPA was a metabolic mediator in the gut that participated in LcS-induced constipation alleviation.